Rainy regions and dry Agriculture in Iraq - Ali Khidher, Salar (Al-Adab Journal, 2019)
The rainfall in Iraq that dry Agriculture depend on it is divided into three regions: limited rainfall (350-200 mm), medium rainfall (500-350 mm) and rain content (500 mm and above). This paper focus on the changes in the boundaries of the dry Agriculture, and it was found through the research that these regions are not stationary, and it is very variable in area. In some seasons some of these regions disappear from the map of Iraq, It was also found that these three regions do not always appear together on Iraq, but sometimes only one or two regions appear . The protected rainfall region (500 mm and above) is subject to expansion in wet seasons to 35.5 ° latitude, while in the dry season it is vanishing and replaced by the region of moderate rain and limited rainfall regions. The medium rainfall region (500-350 mm), whose geographical extension is in the semi-mountainous region, sometimes extends southward to the eastern sections of the alluvial plain near the mountain wall of Zacros. On the other hand the geographical extension of the dry agriculture is limited to rainfall (350-200 mm) is the Mesopotamia Plain, but it is sometimes expanded towards high latitudes, and perhaps the most prominent description of this region is the vast geographical area it occupies, it is a vast territory compared to the former two regions, it appears in all sections of Iraq Mountainous, semi-mountainous, plain and plateau